The Rise and Fall of Michael Henchard in the novel “The Mayor of Casterbridge” by Thomas Hardy A story of a man of character - Sembiring, M.K Baginta (Pascasarjana Universitas HKBP Nommensen, 2022)
There are many determining factors that can be considered as the main cause of success and failure of a certain person in life which is full of challenges. And those who never care for the certain causes of their failure will fall, meanwhile those who want to learn the causes of their failure will rise. It seems so simple if just talk about ‘realize’, but in this context is the person who realizes and determines to change the causes, or at least to suppress them so that they will not be the influential elements for certain failure. “Several critics have pointed to the classical tragic shape of ‘The Mayor of Casterbridge’. It is the story of the rise and fall of a man of character, a man flawed in certain destructive ways; his story is confined in space and time: there clear echoes of Greek tragedy and of King Lear